MISPRICED INDEX OPTION PORTFOLIOS - Constantinides, George M.; Czerwonko, Michal; Perrakis, Stylianos (Financial Management, 2019)
In model-free out-of-sample tests, we find that the optimal portfo lio of a utility maximizing investor trading in the S&P500 Index, cash, and index options bought at ask and written at bid prices stochas tically dominates the optimal portfolio without options and yields returns with higher mean and lower volatility in most months from 1990 to 2013. Unlike earlier claims of overpriced puts, our portfolios include mostly short calls and are particularly profitable when matu rity is short and volatility is high. Similar results are obtained with the CAC and DAX indices. Neither priced factors nor a nonmonotonic stochastic discount factor explains the excess returns.
Keywords: Type of access: Open Access; portfolio